Promoting Translation Competence In Language Teacher Training: Strategies For Equipping Lecturers With Translation Skills For Language Instruction (Journal of Namibian Studies : History Politics Culture, 2023)
The increase in the demand for professionalism in the field of translation over the years has led to the prioritization of translation programs. However, with this program, language educators are equipped with the necessary translation skills for effective language pedagogy. The present study focuses on exploring strategies that can aid language instructors in developing and enhancing their translational skills. While investigating these strategies, it specifically addresses the views of relevant stakeholders on the promotion of translational competence in language teacher training. Nevertheless, the research employed a quantitative methodology, incorporating the collation of various views of relevant stakeholders on the promotion of translational competence in language teacher training. The participants involved in this research are one hundred and three (103) in number; comprising of language lecturers, translation experts and language teacher trainers. On the other hand, the study employed the use of Jamovi statistical software for the computation of the research data, using T-test to validate the two hypotheses formulated for the research. The findings derived from the analysis of the questionnaire responses indicate that curriculum development, task-based learning activities and technology integration are the major strategies for promoting translational competence of language teachers training. Nevertheless, the present study emphasized teaching language teachers to understand cultural nuances, engaging in continuous professional development and having the knowledge of cutting-edge translation tools to help sharpen their translational skills.